2008
DOI: 10.1007/s00203-008-0369-3
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the NrpR regulon in Methanosarcina mazei Gö1

Abstract: The methanogenic archaeon Methanosarcina mazei strain Gö1 contains two homologues of NrpR, the transcriptional repressor of nitrogen assimilation genes recently discovered and characterized in Methanococcus maripaludis. Insertion of a puromycin-resistance conferring cassette into MM1085 encoding a single NrpR domain with an N-terminal helix-turn-helix domain (NrpRI) lead to a significant reduction of the lag-phase after a shift from nitrogen sufficiency to nitrogen limitation. Consistent with this finding, los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 43 publications
0
54
0
Order By: Relevance
“…A single sRNA, GlmY, has been demonstrated to be transcribed by the 54 -RNA polymerase in Escherichia coli, but independently of the global nitrogen transcription regulator NtrC (34). Consistent with nitrogen-regulated transcription of ORFs by the global nitrogen regulator NrpR in M. mazei, 2 of the verified nitrogen-regulated sRNAs contained the NrpR operator in their promoters (8,35). Furthermore, a new motif (box I), which seems to be associated with nitrogen-responsive regulation, was detected up-and downstream of the BRE and TATA-box of 12 sRNA candidates (Fig.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…A single sRNA, GlmY, has been demonstrated to be transcribed by the 54 -RNA polymerase in Escherichia coli, but independently of the global nitrogen transcription regulator NtrC (34). Consistent with nitrogen-regulated transcription of ORFs by the global nitrogen regulator NrpR in M. mazei, 2 of the verified nitrogen-regulated sRNAs contained the NrpR operator in their promoters (8,35). Furthermore, a new motif (box I), which seems to be associated with nitrogen-responsive regulation, was detected up-and downstream of the BRE and TATA-box of 12 sRNA candidates (Fig.…”
mentioning
confidence: 84%
“…Strikingly, most of them seem to be closely related to bacterial proteins (2), whereas the basic components of the archaeal transcription and translation machineries generally are more similar to those of eukaryotes (7). A recent genetic study (8) discovered the first global transcriptional regulator of M. mazei, the nitrogen regulator NrpR, which was experimentally demonstrated to globally repress transcription of nitrogen fixation and assimilation genes in response to the nitrogen source.…”
mentioning
confidence: 99%
“…Genome-wide expression analysis of an M. mazei NrpR1 knockout strain showed elevated transcription of 27 genes under nitrogen sufficiency conditions, including nifH, glnA1, and glnK1 (98). The M. mazei NrpR1 and NrpR2 proteins physically interact and bind as a complex to the nifH and glnK1 promoters in the presence of low 2-OG levels (99).…”
Section: The Archaeal Transcriptional Repressor Nrprmentioning
confidence: 99%
“…Two other DNA binding and repair proteins were found to be upregulated in phase 2 and phase 3 samples compared to phase 1 samples. These included a DNA regulator (Mbar_A1584) involved in transcription (42). General metabo- lism proteins identified in the LTAS study were found to be involved in diverse pathways, including amino acid and vitamin biosynthesis, glycolysis, and electron transport ( Table 3).…”
Section: Resultsmentioning
confidence: 99%